2022
DOI: 10.1111/cbdd.14146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel therapeutic medicine swertiamarin from Enicostema axillare in zebrafish infected with Salmonella typhi

Abstract: Herbal treatments have been practiced by humans over centuries and therefore possess time‐proven safety. However, it is crucial to evaluate the toxic effects of herbal medicine to confirm their safety, particularly when developing therapeutic drugs. Use of laboratory animals such as mice, rat, and rabbits was considered as gold standard in herbal toxicity assessments. However, in the last few decades, the ethical consideration of using higher vertebrates for toxicity testing has become more controversial. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It was found that many plants in Gentianaceae family containing a secoiridoid glycoside, swertiamarin possessed antibacterial properties such as Centaurium species (Bibi et al, 2006;van der Sluis, 1985). and Enicostema species (Perumal et al, 2022;Pillai et al, 2020;Vishwakarma et al, 2004). Moreover, numerous plants containing swertiamarin as the main compound revealed the antimicrobial activity (Niroj et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that many plants in Gentianaceae family containing a secoiridoid glycoside, swertiamarin possessed antibacterial properties such as Centaurium species (Bibi et al, 2006;van der Sluis, 1985). and Enicostema species (Perumal et al, 2022;Pillai et al, 2020;Vishwakarma et al, 2004). Moreover, numerous plants containing swertiamarin as the main compound revealed the antimicrobial activity (Niroj et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of multidrug resistance to the frequently used antibiotics has further convoluted the treatment and management of typhoid fever and this has documented as one of the utmost challenges in managing the disease. 4 Various factors contribute towards the cases and deaths due to typhoid fever among people. These factors include no access to drinking water, absence of proper sanitation and unhygienic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Smolii et al from Ukraine reported the discovery of novel fused 7‐deazaxanthine derivatives as adenosine A 2A receptor antagonists (Muzychka et al, 2021). Lastly, Subramanian et al reported that Swertiamarin, isolated from Enicostema axillare , showed antimicrobial activity in zebra fish larvae against Salmonella typhi and cleared the bacterial load and pathogenic symptoms (Perumal et al, 2022).…”
mentioning
confidence: 99%